South Africa’s intervention in Angola: Before Cuito Cuanavale and thereafter - Labuschagne, Bernice (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MA (Political Science. International Studies))--University of Stellenbosch, 2009.